OCLC / PICA – A New European Organisation to Build Transatlantic Library Cooperation - Lees, Janet Mitchell (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
Today I would like to explore some of the issues relating to transatlantic library cooperation as an important element within the concept of global library cooperation. I would like to explore some of the issues and indeed some of the barriers and to discuss this within the context of the new OCLC Pica European library organisation.